A genetic safeguard for eliminating target genes in synthetic probiotics in a gut environment - Nhu Nguyen; Miaomiao Wang; Lin Li; Clement T.Y. Chan (iScience)
Summary: To meet the emerging demand for constraining engineered probiotic activities, many biocontainment studies explore strategies that involve killing engineered microbes, which often create basal levels of cytotoxicity that hamper cell fitness and performance. Here, we explored a circuit design that destroys the engineered genetic materials in a probiotic strain, instead of killing these cells, under non-permissive conditions. Our safeguard circuit involves a two-layered transcriptional regulatory circuit to control the expression of a CRISPR system that targets the engineered genes for degradation. In Escherichia coli Nissle 1917 (EcN), the biocontainment system did not hamper cell fitness, and it continuously scavenged and destroyed the target, promoting complete elimination of engineered genetic materials and activities. We demonstrated that the engineered probiotics maintained its activities for 7 days in a mouse model when the permissive signal was supplied constantly, but the activities became undetectable within two days upon the cease of signal supply.